Topical beta-blocker therapy sheds new light on the natural history of pyogenic granuloma. - Mazzotta, F.; Troccoli, T.; Milano, A.; Pisani, V. (European Journal of Pediatric Dermatology, 2023)
Pyogenic granuloma is a reactive proliferation of angiopoietic endothelial cells to usually unobvious stimuli; it is characterized by rapid growth leading to profuse bleeding. To avoid this worrying event, pyogenic granuloma is usually removed and for this reason we do not know its natural history, unlike other vascular proliferations. Since the efficacy of beta-blockers on infantile hemangioma was discovered, many dermatologists have used them in pyogenic granuloma especially for topical use after surgical removal to prevent frequent recurrences or even as substitutes for surgery. The current work reported the clinical observations on 21 cases of pyogenic granuloma observed between May and November 2018 in which, when possible, topical treatment with timolol was started; when removal was necessary, this was followed by topical therapy with timolol. The report showed that pyogenic granuloma can regress without any therapy, that surgery can be avoided in about a third of cases, and that timolol can favor the regression of pyogenic granuloma and prevent recurrences.